Continuums of Change in a Competence-Building Initiative Addressing End-of-Life Communication in Swedish Elder Care. (August 2021) - Johansson, Therese; Tishelman, Carol; Cohen, Joachim; Eriksson, Lars E.; Goliath, Ida
Conversations about values for the end-of-life (EoL) between residents, relatives, and staff may allow EoL preparation and enable value-concordant care, but remain rare in residential care home (RCH) practice. In this article, longitudinal qualitative analysis was used to explore changes in staff discussions about EoL conversations throughout workshop series based on reflection and knowledge exchange to promote EoL communication in RCHs. We identified three overall continuums of change: EoL conversations became perceived as more feasible and valuable; conceptualizations of quality EoL care shifted from being generalizable to acknowledging individual variation; and staff's role in facilitating EoL communication as a prerequisite for care decision-making was emphasized. Two mechanisms influenced changes: cognitively and emotionally approaching one's own mortality and shifting perspectives of EoL care. This study adds nuance and details about changes in staff reasoning, and the mechanisms that underlie them, which are important aspects to consider in future EoL competence-building initiatives.